An Analysis of the Presentation of the Image of King Henry VIII of England and His Prominent Advisors - Taylor, Mary (My University, 2015)
If you were to ask virtually any person in the park to describe Henry VIII of England, the response you would get would probably include words such as "tyrant", "glutton", "ill-tempered", "cruel", and so on; this is how the public remembers this notorious king. Historically, he could perhaps be described this way in his later years but hardly in his prime. This paper examines the differences between what historians have concluded, specifically about Henry VIII and his close advisers Cardinal Thomas Wolsey and Thomas Cromwell, cinematic and television adaptations, and published summations of events and people, which seem to dictate the public's knowledge of history. How is each one of these important men depicted in shows like BBC's The Tudors, and books throughout history like John Richard Green's 19th century Short History of the English People? What role do popular documentaries like Inside the Court of Henry VIII directed by Peter Chinn, PBS's Secrets of Henry VIII's Palace: Hampton Court, and PBS?s Tales From the Royal Bedchamber play in this discussion? This paper addresses these issues.
Keywords: Great Britain -- Kings and rulers -- Biography -- Drama; Great Britain -- History -- Henry VIII, 1509-1547; Cromwell, Thomas, Earl of Essex, 1485?-1540; Wolsey, Thomas, 1475?-1530; Henry VIII, King of England, 1491-1547